kemunculan identitas kelompok dalam industri kaos dablongan banyumasan - neny marlina (Jurnal Lingua Idea, 2017)
The title of the research is “the emergence of collective identity in Dablongan Banyumasan shirt industry.” The location of the research was in Banyumas Regency of Central Java Province, with the objective of descripting the emergence of collective identity through local shirt industry particularly Banyumasan special shirt of Dablongan. The politic of identity in the research would not be seen as threat, but on the contrary it is considered as opportunity in social harmonization as well as the chance to display the products of creative industries. The method of research is qualitative research method and the informan withdrawal is based on purposing sampling. The data are coming from primary data and secondary data. Data primer are gained from depth interview and observation, while secondary data are collected from documentation. The emergence of raising cultural identity through language, picture, and other designs local shirt to resurface the basic local characteristic gives positive impacts as well as the negatives. The resurgence of collective identity who are proud of their local culture gives positives influence on the existence of the local cultures in Indonesia. Nevertheless, if the sense of locality is too much, it will create contested identity with other local identities along with the forsaking of the idea that local identities are actually parts of national identity. Creative industry needs three primary actors, government, business, and intellectuals to drive the industry stay in its lane. Government needs to give guidelines and appreciation toward creative industry which able to compete to the foreign culture. The business is needed to manage the fiscal as well as the marketing of creative industry, and the intellectuals are needed to give deeper understanding on the local culture which become business opportunity but do not threat the existence of other local cultures.